2022
DOI: 10.3390/ijerph19031574
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Associated with Unfavorable Outcomes among Drug-Resistant TB Patients: A 6-Year Retrospective Study from Pakistan

Abstract: The spread of drug-resistant tuberculosis (DR TB) poses significant challenges to the control and successful eradication of TB globally. The current retrospective study was designed to evaluate the treatment outcomes and identify the risk factors associated with unsuccessful outcomes among DR TB patients. A total of 277/308 eligible DR TB patients were enrolled for treatment at the programmatic management unit of DR TB at the Pakistan Institute of Medical Sciences, Islamabad between January 2014 and July 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
6
12
1
Order By: Relevance
“…In multivariate analysis the emergence of patients age of 41-60 and > 60 years as predictors of unsuccessful end treatment outcomes among MDR-TB patients is in line with the previous studies (Kurbatova et al, 2012;Ahmad et al, 2015;Khan et al, 2019;Atif et al, 2020;Wahid et al, 2021). The concomitant presence of multiple factors like general physical deterioration, compromised immunity, multiple comorbidities, and complex medication schedule make older patients more likely to develop unsuccessful treatment outcomes (Kurbatova et al, 2012;Ahmad et al, 2015;Khan et al, 2019;Atif et al, 2020;Wahid et al, 2021;Khan et al, 2022b). In the current study, those patients who had a baseline body weight of > 30 kg were significantly less likely to develop unsuccessful treatment outcomes than their counterparts with a baseline body weight of <30 kg.…”
Section: Discussionsupporting
confidence: 82%
“…In multivariate analysis the emergence of patients age of 41-60 and > 60 years as predictors of unsuccessful end treatment outcomes among MDR-TB patients is in line with the previous studies (Kurbatova et al, 2012;Ahmad et al, 2015;Khan et al, 2019;Atif et al, 2020;Wahid et al, 2021). The concomitant presence of multiple factors like general physical deterioration, compromised immunity, multiple comorbidities, and complex medication schedule make older patients more likely to develop unsuccessful treatment outcomes (Kurbatova et al, 2012;Ahmad et al, 2015;Khan et al, 2019;Atif et al, 2020;Wahid et al, 2021;Khan et al, 2022b). In the current study, those patients who had a baseline body weight of > 30 kg were significantly less likely to develop unsuccessful treatment outcomes than their counterparts with a baseline body weight of <30 kg.…”
Section: Discussionsupporting
confidence: 82%
“…Multidrug TB treatment has long therapy duration (18 months to 2 years), and the number of drugs used for the treatment is comparatively more complex than that for drug-susceptible TB ( Khan et al, 2022 ). Numerous side effects are identified that result in patients’ non-compliance and predictably poor outcomes ( Tahaoğlu et al, 2001 ; Mukherjee et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…This partially might be attributed to a shortage of TB management staff, lengthy treatment courses, side effects associated with anti-TB drugs, resistance to first-line anti-TB drugs, and the disappearance of signs and symptoms of TB after partial anti-tuberculosis treatment (ATT) ( Atif et al, 2014 ; Atif et al, 2017a ). Alongside poor health literacy, stigma associated with the disease, and poor financial status of TB patients and their families, these factors further complicate the TB treatment cascade ( Khan et al, 2022a ). In addition, inequality in healthcare services and/or limited access to alternative treatment, for example, for patients residing in rural areas or distant areas, halts the achievement of national TB-related targets ( Khan et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside poor health literacy, stigma associated with the disease, and poor financial status of TB patients and their families, these factors further complicate the TB treatment cascade ( Khan et al, 2022a ). In addition, inequality in healthcare services and/or limited access to alternative treatment, for example, for patients residing in rural areas or distant areas, halts the achievement of national TB-related targets ( Khan et al, 2022a ). With regard to healthcare professionals, Pakistan’s Ministry of Finance in Economic Survey 2020–2021 indicated that a single physician caters to the needs of hundreds of patients requiring treatment ( Ministry of Finance, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation